Performance investigation and optimization of ejector and vapor compression cycle: integrated sCO2 trigeneration systems - Cetin, T.H (2024)
Growing concern on climate change urges to seek an efficient, sustainable and economic energy supply. The domestic sector accounts for 40% of the primary energy consumption globally and 36% of the greenhouse gas emissions. Supercritical carbon dioxide technology is one of promising candidates for providing solutions to climate change. In this thesis, the performance investigation of two trigeneration systems based on supercritical CO2 (sCO2), vapor compression sCO2 recuperation system (VCRS) and ejector-integrated sCO2 recuperation system (EIRS), is conducted from first and second laws of thermodynamics point of view as well as thermoeconomic point of view. Sources of the irreversiblilites of the systems are identified and costs of these inefficiencies are quantified by using thermoeconomic analysis. For both systems, recuperator is the main source of irreversibility in the power cycle section. For the refrigeration section, electric compressor and expansion valve are the main sources of irreversibility with costs of exergy destruction value of 1.11£/h and 0.93£/h for VCRS configuration, and these deficiencies are reduced by using ejector instead of expansion valve. For the EIRS configuration, electric compressor cost of exergy destruction value is reduced to 0.975£/h and expansion valve’s cost of destruction value is decreased to 0.007£/h. Multi-objective optimization is carried out in order to maximize exergetic efficiency while minimizing exergetic cost of products, the lowest rate of exergy cost and minimum exergy efficiency can be achieved at the same time. For the VCRS, the minimum exergy cost rate is 14.11£/h, aligning with the smallest exergy efficiency of 59.47%. Similarly, for the EIRS, the minimum exergy cost rate is 13.15£/h, coinciding with a low exergy efficiency of 47.54%. In order to investigate annual performance of VCRS and EIRS configurations, detailed models of heat exchanger, turbomachinery and heating block components are developed. The turbomachinery is key component of the sCO2 system, so it’s off-design behaviour in the system performance map is clarified by a novel turbomachinery design tool, TΔhC, and its inventory control scheme is adopted. In the annual performance simulation, the directly heated solar/biomass powered system with 400kWth cooling output is considered. For the VCRS configuration, the winter season sees an average of 80,635kWh of electricity supplied to the grid per month, this figure rises to 118,210 kWh during the summer season, the solar share is 11.87% and payback period is 8.37 years. For the EIRS configuration, during the winter period, the system fed an average of 85,212 kWh of electricity into the grid per month, while in the summer period, the monthly average electricity export to the grid increases to 125,640 kWh, the solar share is 14.59% and payback period of the system is 8.49 years. Keywords: Supercritical CO2, trigeneration, vapor compression, ejector cooling